Least Square Method for Solving Second-Order Eigenvalue Problems with Nonlinear Delay Involves Ordinary Differential Equations with Nonlinear Delay - Huda Farg Alspihe; Hala Ail Shelo (African Journal of Advanced Pure and Applied Sciences, 2025)
The objective of this research is to survey nonlinear eigenvalue problems of the second order with delay, which are considered one of the known expansion methods, involving ordinary differential equations with delay. To solve this type of problem, one of the known expansion methods known as the least squares method, will be advanced.